Faktor-Faktor yang Mempengaruhi Fleksibilitas Keuangan (Studi Kasus yada Perusahaan yang Terdaftar pada Bursa Efek Indonesia (Periode 2008-2012)) - Murti, Adytia Pradnya; Achsani, Noer Azam; Andati, Trias (Jurnal Aplikasi Manajemen, 2016)
This study aimed to determine the capital position and company's performance in Indonesia during the 2008-2012 period and to determine the factors that affected the company's financial flexibility in Indonesian firms. The samples of this study were 45 largest capitalized company listed on the Jakarta Stock Exchange.This study used synthetic rating and the debt service coverage ratio to determine the company's capital position and performance, and used panel data to determine the factors that affected financial flexibility. The results showed that existence a decrease in the default rate, in 2008 the average default rate was 6.12%, in 2009 decreased to 3.99%, in 2010 down to 2.91%, and then in 2011 and 2012 slightly increased to 3.17% and 3.30 %. Based on the results of panel data the factors that affected the financial flexibility is Leverage Ratio, Free Cash Flow, and crisis.